Identification of Putative Chemosensory Receptor Genes from the Athetis dissimilis Antennal Transcriptome. - Junfeng Dong; Yueqin Song; Wenliang Li; Jie Shi; Zhenying Wang (PLoS ONE, 2016)
Olfaction plays a crucial role in insect population survival and reproduction. Identification of the genes associated with the olfactory system, without the doubt will promote studying the insect chemical communication system. In this study, RNA-seq technology was used to sequence the antennae transcriptome of Athetis dissimilis, an emerging crop pest in China with limited genomic information, with the purpose of identifying the gene set involved in olfactory recognition. Analysis of the transcriptome of female and male antennae generated 13.74 Gb clean reads in total from which 98,001 unigenes were assembled, and 25,930 unigenes were annotated. Total of 60 olfactory receptors (ORs), 18 gustatory receptors (GRs), and 12 ionotropic receptors (IRs) were identified by Blast and sequence similarity analyzes. One obligated olfactory receptor co-receptor (Orco) and four conserved sex pheromone receptors (PRs) were annotated in 60 ORs. Among the putative GRs, five genes (AdisGR1, 6, 7, 8 and 94) clustered in the sugar receptor family, and two genes (AdisGR3 and 93) involved in CO2 detection were identified. Finally, AdisIR8a.1 and AdisIR8a.2 co-receptors were identified in the group of candidate IRs. Furthermore, expression levels of these chemosensory receptor genes in female and male antennae were analyzed by mapping the Illumina reads.